Selviytymistä vai suorituskykyä? Terveydenhuolto organisoinnin, tiedonhallinnan ja henkilökunnan kannalta; Survival or Performance? Healthcare Viewed Through Organization, Information Management, and Personnel - Antti Kauhanen; Martti Kulvik; Sirpa Maijanen; Olli Martikainen; Paula Ranta; Silja Kulvik (The Research Institute of the Finnish Economy (ETLA), 2013)
– This report is an overview to the presentations and discussions in the seminar Survival or performance? Healthcare viewed through organization, information management, and personnel held on 3.9.2012. The seminar provided an interdisciplinary forum for the question how the health care system may overcome its present challenges.
Keywords: I11; I12; M15; 330; Health care; Work organization; Processes; Information technology; Gesundheitswesen; Arbeitsorganisation; Informationsmanagement; IT-Infrastruktur